Enhanced Reforming of Tar Based on Double-Effect Ni/CaO–Ca12Al14O33 Catalysts: Modified by Ce, Mg, and Fe - Wang, Panlei; Zhang, Weidong; Yu, Zhenyu; Xie, Huaqing; Zhou, Mi; Wang, Zhengyu (Frontiers in Energy Research, 2021)
The double-effect Ni-based catalysts with Ce, Mg and Fe modified respectively, synthesizing by coprecipitation method, were applied into the enhanced steam reforming process of real tar. By the catalyst, the effects on H2 yield, H2 and CO2 concentrations with different doping mass ratios (3%, 6%, 9% and 12%) of Ce, Mg and Fe were studied. The results revealed that the tar reforming efficiency was improved with appropriate proportion of the additives added. For Ce or Mg doping catalyst, it could change the distribution or morphology of the active component Ni. The modified catalyst with 6% Ce or 3% Mg doped showed the best catalytic activity in the reforming experiment, with the H2 yield reaching 86.84% or 85.22%, respectively. For Fe doping catalyst, it could form Ni-Fe alloy and improve the stability of the catalyst, and the better catalytic activity can be obtained at 9% and 12% Fe doped, with the H2 yield reaching 85.54% and 85.80%, respectively.